Equiano Narratives: An Historical Inquiry into Igbo Drinking Culture - Okonkwo, Uche Uwaezuoke (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
The drinking habits of the lgbo people changed with their contact with Europeans around 1600s through their coastal neighbours. Prior to this contact, the only alcoholic brand known to the people was palm wine. Prominent Igbo merchants such as the Aro played vital role in spreading European trade goods such as alcohol in exchange for slaves, As a result of the absence of written source ,Equaino narratives of 1789 offers a useful alternative in understanding the fact that the Europeans importation of brands such as Schnapps, Brandy, Whiskey, Rum, etc altered the cultural habits of the people with regards to alcohol use. Using Equiano narratives therefore, this paper concludes that Igbo people were moderate alcohol drinkers relying solely on palm wine prior to their contact with Europeans.